Implementation of Pancasila Student Profile Values in Elementary Schools in Facing Society 5.0 - Asri Mulyani; Bunyamin; Agus Muharam (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The number of social deviations that occur such as increasing cases of brawls, harassment, and vandalism indicates a decline in moral values in the nation's children. These things cannot be separated from the negative impact of the use of information and communication technology. This study aims to conduct a literature review related to the implementation of Pancasila student profile scores in elementary schools in facing society 5.0. This research is qualitative by using the SLR (Systematic Literature Review) method. Data collection is done by documenting and reviewing all articles related to Pancasila Student Profile Values published in the 2020-2022 period. The articles used in the study were 20 journal articles. Based on this study, it was found that the value of the Pancasila profile is 1) have faith, fear God Almighty, 2) global diversity, 3) work together, 4) be independent, 5) critical reasoning, and 6) creative. So it can be concluded that the Value of the Pancasila Student Profile in elementary schools can be used in dealing with society 5.0.